2014
DOI: 10.1167/iovs.13-13372
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Inner Retinal Neurons After Retinal Ischemia in Rats

Abstract: PURPOSE. Ischemia is a risk factor for eye diseases like ocular vein occlusion or glaucoma. To investigate effects of ischemia-reperfusion (I/R) a lot of different animal models are used, studying one or two different cell types, which creates heterogeneity of data. The aim of this study was to investigate the function and morphology of the whole retina and different retinal cell types in an I/R model. METHODS. I/R was induced by elevating the intraocular pressure in the right eyes of rats. Twenty-one days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
104
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 45 publications
9
104
3
1
Order By: Relevance
“…In the present study, the number of cells in the RGC and the thickness of the IRL were decreased after IR injury. In the study by Schmid et al [27], the number of cells in the GCL and the thickness of the inner plexiform layer induced by ischemia had a significant reduction and there was no difference in rod bipolar cell numbers. Our result is consistent with this research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the number of cells in the RGC and the thickness of the IRL were decreased after IR injury. In the study by Schmid et al [27], the number of cells in the GCL and the thickness of the inner plexiform layer induced by ischemia had a significant reduction and there was no difference in rod bipolar cell numbers. Our result is consistent with this research.…”
Section: Discussionmentioning
confidence: 99%
“…The increased level of cleaved caspase-3 in the ischemic eye indicated that apoptosis plays a major role in RGC degeneration. Other studies also investigated the expression of cleaved caspase-3 in an IR model and likewise found a significant increase of cleaved caspase-3 RGCs in ischemic eyes [27]. It is well known that caspases are a family of intracellular proteins involved in the initiation and execution of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Die Schichtanalyse konnte zeigen, dass die parafoveoläre Verminderung der Netzhautdicke in erster Linie auf eine Verdünnung der Ganglienzellschicht, der inneren plexiformen sowie der inneren Körnerschicht zurückzuführen war. Dies passt zu Ergebnissen experimenteller Untersuchungen, in denen ischämische Veränderungen in den Bereichen der inneren Netzhaut auch im Tiermodell nachgewiesen werden konnten [8].…”
Section: Diskussionunclassified
“…However, it is known that apoptosis plays an important role (18). One study revealed that cells in the inner retina especially RGCs are more vulnerable to ischemic damage compared to cells of the outer retina (19). Apoptosis, as detected by TUNEL staining, has been observed in the GCL, INL, and outer nuclear layer of the retina (20).…”
Section: Discussionmentioning
confidence: 99%